Letter - Kings Lynn Trades Council and Local Labour Party, 11 May 1926 (Kings-Lynn)
1926-05-11 "Letter - Kings Lynn Trades Council and Local Labour Party, 11 May 1926" [g0353001.jpg], 11 May 1926, Kings Lynn Trades Council and Local Labour Party Local Organisation